2011
DOI: 10.1007/s13197-010-0209-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selected dehulled legume incorporation on functional and nutritional properties of protein enriched sorghum and wheat extrudates

Abstract: The effect of legume incorporation (5%, 10% and 15%) on functional and nutritional properties of sorghum and wheat extrudates was investigated. Sorghum extrudates incorporated with legumes showed lower water absorption index water solubility index and pasting properties viz., peak viscosity, minimum viscosity, breakdown viscosity, final viscosity and total set back and similar degree of gelatinization and nutritional profile. At 15% incorporation level, water absorption index and water solubility index found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Extruded products are extensively studied (Balasubramanian et al 2012;Eastman et al 2001;Parker et al 2000;Guha and Ali 2006) signifying wide acceptability. However, the characteristics of starch based extrudates depend on many factors, such as feed moisture and lipid content, additives and variables like screw speed, barrel temperature and type of extruder (Jin et al 1995;Suknark et al 1997;Singh et al 1998;Singh et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Extruded products are extensively studied (Balasubramanian et al 2012;Eastman et al 2001;Parker et al 2000;Guha and Ali 2006) signifying wide acceptability. However, the characteristics of starch based extrudates depend on many factors, such as feed moisture and lipid content, additives and variables like screw speed, barrel temperature and type of extruder (Jin et al 1995;Suknark et al 1997;Singh et al 1998;Singh et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics are quantified by functional properties like bulk density, expansion index, water absorption and solubility indices and viscosity of the product (Singh et al 2007;Oikonomou and Krokida 2011). The effects of extrusion conditions and feed compositions on functional properties of various cereal and pulse based products have been studied extensively (Balasubramanian et al 2012;Seth and Rajamanickam 2012). Several studies found that increasing feed moisture content increases the bulk density, water solubility index, water absorption index and hardness and decreases the expansion ratio (Chiu et al 2012;Kirjoranta et al 2012;Oke et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the third experiment, the feed rate was adjusted as follows: 20.0, 30.0, 40.0, 50.0, and 60.0 g·min −1 , while the barrel temperature and the feed moisture content were fixed at T3 and 20.0%, respectively. The range of independent variables was established on the basis of previous studies [ 47 , 48 ] and preliminary trails.…”
Section: Methodsmentioning
confidence: 99%
“…The WAI and the WSI of the whole-wheat flour samples extruded under different conditions was measured according to the method developed by Balasubramanian et al [ 48 ], with minor modifications. Here, 2.0 g of the ground extrudates was combined with 25 mL of distilled water in a beaker at room temperature while gently stirring for 30 min with a magnetic stirrer (86-1, Sile, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation